A methodology for selecting and defining maintenance tasks for critical equipment - Sousa, M. (2018)
This paper presents a methodology, developed through a case study, to support preventive maintenance tasks selection based on Reliability Centered Maintenance (RCM) methodology. The case study was carried out in an electronic goods company that follows the Total Productive Maintenance (TPM) philosophy. The methodology has six steps and it is intended to be applied in every mechanical and electro-mechanically equipment of the plant and it is applicable in equipment with some historical data of interventions. To validate the methodology, one system of the plant was selected and all the steps of the methodology were followed. With this application, a reduction of 33% in failures number and production losses was achieved, as well as a MTBF improvement of about 15% and therefore an increase in machine yield.